PERENCANAAN KEBUTUHAN TEMPAT TIDUR DI RUMAH SAKIT PARU JEMBER TAHUN 2013-2015 - Tika Maretanata Pujianti; Dian Damayanti; Feby Erawantini (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2014)
ABSTRACTJember Pulmonary Hospital is one of hospital which conducts the ten big pulmonary tuberculosis morbidityrates. In last three years, Jember Pulmonary Hospital increases the number of patients. Prediction the numberof pulmonary TB morbidity is needed for planning the requisite of facility related with TB that one exceptionis planning of patients bed requirement. The survey design is kuantitatif descriptive.This prediction use trendanalysis method for counting the forecast number of pulmonary TB morbidity and for 2013-2015’s planning.This research review based on two variables: age and gender with a total population of 1056 patients. Thepurpose of this study is doing the calculation of the pulmonary tuberculosis morbidity for three years (2013-2015) by using analysis of trends method. by the age variable, the factual result of this research are: patientswho classified as children (0-14 years old) in 2013 were 3,6%, at 2014 were 3,7% and in 2015 were 3,8%;Adulthood (15-64 years old) in 2013 were 87,2%, at 2014 were 86,9% and in 2015 were 86,7%; elderly(≥65 years old) in 2013 were 9,1%, 2014 totaled 9,2% and 2015 totaled 9,4%. Based on the variables ofgender; the patients who classified in male in 2013 were 56,1%, in 2014 were 56,5%, in 2015 were 56,9%;the patient who classified in female in 2013 were 43,8%, in 2014 were 43,3% and in 2015 were 43,01%. Whilethe requirement of patient’s bed that needed in 2014 were 65 beds, and it still need three additional beds , in2015 need 70 beds that’s why it’s needed eight additional beds. The solution that can be given to the hospitalis the hospital management needs to rearrange the budget for beds and other facilities as well that supportsmedical service programs in hospital.Kata kunci: Forecasting, Tuberculosis Morbidity